Սիոնիզմը և Հայոց ցեղասպանությունը - Յաիր Արոն (ՀՀ ԳԱՍ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
Задача данной статьи на основе исследованных автором документов, свидетельств времен Первой мировой войны - попытаться представить отношение к вышеупомянутой проблеме "Юишува" (еврейская община в Палестине до 1948г.), сионистического движения и нынешних официальных властей Израеля. The task of the article is to try and present the attitude of Uishuv (Jewish community in Palestine before 1948), Zionistic movement and the present official authorities of Israel to the above-mentioned problem based on examination of documents, testimonies from the times of World War I.
Keywords: Պատմագրություն; Հայոց ցեղասպանություն (1915)